Of mice and men: neurogenesis, cognition and Alzheimer’s disease - Lazarov, Orly; Marr, Robert (Frontiers in Aging Neuroscience, 2013)
Neural stem cells are maintained in the subgranular layer of the dentate gyrus and in the subventricular zone in the adult mammalian brain throughout life. Neurogenesis is continuous, but its extent is tightly regulated by environmental factors, behavior, hormonal state, age and brain health. Increasing evidence supports a role for new neurons in cognitive function in rodents. Recent evidence delineates potential significant differences between adult neurogenesis in rodents and humans. Being context-dependent, neurogenesis in the human brain might be manifested differently than in the rodent brain. Decline in neurogenesis may play a role in cognitive deterioration, leading to the development of progressive learning and memory disorders, such as Alzheimer’s disease. This review discusses the different observations concerning neurogenesis in the rodent and human brain, and their functional implications for the healthy and diseased brain.